Anxiety and Coping Strategies: The Adequate and Integrative Review - Powar, Vishal (Indian Journal of Nursing Sciences, 2024)
Stress has become part of students’ academic life due to the various internal and external expectations placed on their shoulders. Adolescents are particularly vulnerable to the problems associated with academic stress as transitions occur at an individual and social level. It, therefore, becomes imperative to understand the sources and impact of academic stress to derive adequate and efficient intervention strategies. Understanding the sources of stress would facilitate the development of effective counseling modules and intervention strategies by school psychologists and counselors to help students alleviate stress. Anxiety in nursing students negatively impacts academic as well overall success. This review highlights anxiety and coping strategies in nursing students.